2015
DOI: 10.1007/s11693-015-9182-x
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic biology puzzle: a qualitative study on public reflections towards a governance framework

Abstract: Synthetic biology is currently one of the most debated emerging biotechnologies. The societal assessment of this technology is primarily based on contributions by scientists and policy makers, who focus mainly on technical challenges and possible risks. While public dialogue is given, it is yet rather limited. This study explores public debates concerning synthetic biology based on a focus group study with citizens from Austria and Germany and contextualises the analysed public views with content from policy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…At the same time, interest in what the public will think continues [e.g. Starkbaum, Braun and Dabrock, 2015;Pauwels, 2009;Pauwels, 2013;Torgersen and Schmidt, 2013]. And policy meetings continue to be held on behalf of public safety [Cho and Relman, 2010;Kuiken, 2015].…”
Section: Ethical Question and Public Awarenessmentioning
confidence: 99%
“…At the same time, interest in what the public will think continues [e.g. Starkbaum, Braun and Dabrock, 2015;Pauwels, 2009;Pauwels, 2013;Torgersen and Schmidt, 2013]. And policy meetings continue to be held on behalf of public safety [Cho and Relman, 2010;Kuiken, 2015].…”
Section: Ethical Question and Public Awarenessmentioning
confidence: 99%
“…Loans are instances where certain claims are being suspended and can be reclaimed at the conclusion of the loan (on the significance of this picture for understanding public attitudes towards scientific research, cf. Starkbaum et al 2015;Braun and Dabrock 2016b). Other claims can remain in place throughout, e.g., when there are expectations about the purpose of the loan.…”
Section: Observation IImentioning
confidence: 99%
“…This highlighted low certainty of these participants' attitudes, partly due to a lack of information and media attention (Fischer et al , 2013). In research into specific applications, it has been reported that applications for medical and environmental use tended to be more in line with public preference than agricultural and food products (Ineichen et al , 2017; Starkbaum et al , 2015; Steurer, 2015).…”
Section: Introductionmentioning
confidence: 99%